Unworthy of the blue shirt: The repression of sexual immorality in women of the Spanish Fascism (1938-1943) - Barrera López, Begoña (Historia y Política, 2025)
The purpose of this article is to explore, from a gender perspective, the way Spanish male fascists interpreted the sexual transgressions committed by their female comrades in the single party FET de las JONS. To achieve this, it draws on a sample of disciplinary files on female Falangists initiated between 1938 and 1943. In these records, the Falangists were accused of being «frivolous», «licentious», or «prostitutes », and consequently processed for «degrading or offensive conduct». The analysis of this documentation yields two main conclusions intended to contribute to the debate on power relations within Spanish fascism. First, that the internal justice of FET-JONS operated as an effective disciplinary mechanism in internal repression against their own members for any violation of the gender order. Second, that the female Falangists, aligned with the victors and beneficiaries of the privileges that their affiliation provided them over ordinary women, were simultaneously victims of the policies and inequality, in the form of a sexual double standard, that they were supporting with their militancy.